2009
DOI: 10.1159/000201327
|View full text |Cite|
|
Sign up to set email alerts
|

High Dose Magnesium Sulfate Exposure Induces Apoptotic Cell Death in the Developing Neonatal Mouse Brain

Abstract: Background: Magnesium sulfate (MgSO4) is often used as a treatment for pre-eclampsia/eclampsia and preterm labor, resulting in the exposure of a significant number of neonates to this drug despite a lack of evidence suggesting that it is safe, or effective as a tocolytic. While there is evidence that MgSO4 may be neuroprotective in perinatal brain injury, recent reviews have suggested that the effects are dependent upon dose, and that higher doses may actually increase neonatal morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 68 publications
6
43
2
3
Order By: Relevance
“…The studies that investigated the potential neuroprotective effect of magnesium have revealed conflicting data [3,[6][7][8][9][10][11][12][13][14][15][16][17] . MgSO 4 given 1, 12 and 24 h after HI insult did not decrease the severity of delayed cerebral energy failure [12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that investigated the potential neuroprotective effect of magnesium have revealed conflicting data [3,[6][7][8][9][10][11][12][13][14][15][16][17] . MgSO 4 given 1, 12 and 24 h after HI insult did not decrease the severity of delayed cerebral energy failure [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Results: Percent infarcted brain volume was significantly reduced in pups receiving the drugs (either magnesium sulfate, melatonin or their combi-Magnesium sulfate (MgSO 4 ) is an NMDA receptor antagonist which prevents excitotoxic calcium-induced injury through the noncompetitive voltage-dependent inhibition of NMDA receptor, which reduces calcium entry into the cell [5] . Although conflicting data exist on the beneficial effects of magnesium in experimental and clinical neonatal HI models [6][7][8][9][10][11][12][13][14][15][16][17] , magnesium bears major advantages as a neuroprotective agent in that it can be safely administered to newborn infants with severe perinatal asphyxia [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the recent article by Dribben et al [1] , which we believe is important and has several implications. Firstly, this article demonstrates that the effects of magnesium sulfate are age-and model-dependent.…”
mentioning
confidence: 96%
“…Taken together, the studies of Dribben et al [1] , Krueger et al [4] and Mikati et al [5] argue that further investigations to understand the effects of MgSO 4 on the newborn, as well as the adult (eclamptic mother), should be a priority. They also argue that large scale controlled prospective clinical studies examining these effects are still very much needed.…”
mentioning
confidence: 99%
“…Ketamine-induced apoptosis is enhanced by cotreatment with diazepam or midazolam in a rodent model (Fredriksson et al, 2004;Young et al, 2005), but diazepam has still been long used to alleviate psychotomimetic adverse effects of ketamine in humans. In addition, magnesium loading that has been used in (pre)eclampsia, may be neurotoxic for the developing nervous system (Dribben et al, 2009), and at least one clinical trial with MgSO 4 supplementation to pregnant women with preterm labor had to be preliminarily stopped due to increased pediatric mortality (Mittendorf et al, 1997), especially to neonatal intraventricular hemorrhage (Mittendorf et al, 2002). These last cases are just two examples of problems recently encountered in the treatment affecting negatively the developing fetal or neonatal brain.…”
mentioning
confidence: 99%